Assessing the Welsh Government's consultation on reforms to council tax - Stuart Adam; David Phillips; Sam Ray-Chaudhuri (Institute for Fiscal Studies (IFS), 2023)
We analyse the impact of the possible approaches to council tax reform set out in the Welsh Government's consultation on "A fairer council tax".
Keywords: 330; Government finances and spending; Taxes and benefits; Devolution; Devolved government finances; Geography; Inequality; Local government finance; Tax; Property taxes; Wales